Comparison of Early Versus Delayed Weight-bearing Outcomes after Ankle Fractures Surgical Treatment; A Retrospective Analytical Study: Rehabilitation after Ankle Fracture - Zandi, Reza; Minator Sajjadi, Mohammadreza; Boland Nazar, Najmeh sadat; Mohammadaliahmad, Reza (Journal of Clinical Physiotherapy Research, 2021)
Introduction: This study aimed to evaluate the early and delayed weight-bearing outcomes in patients with ankle fractures who underwent surgical treatment. Materials and Methods: This retrospective analytical study was conducted on 38 patients with bimalleolar ortrimalleolar fractures referred to Taleghani Hospital, Tehran, Iran. Patients who underwent ankle fracture surgical treatment were divided into the early weight-bearing group (study group) and the delayed weight-bearing group (comparison group). The outcomes were functional factors including pain, bulging, running, support, daycare, and stiffness were assessed and compared between the groups. Data were analyzed by IBM SPSS Statistics ver.23 at significant level of P-values <0.05. The Kolmogorov-Smirnov test approved the normality of data. Chi-squared test and independent T-Test were used to compare the outcomes between the groups. Results: Out of 38 patients, 30 were men (79%), and 8 were female (21%), with a mean age of 32.12 ±1.22 years old (range: 17 to 58 years). Contrary to the comparison group (delayed weight-bearing), pain (P=0.006), running (P=0.035), support (P=0.003), daycare (P=0.001), and total scores (P=0.001) were significantly higher in the intervention group (early weight-bearing) two weeks after the surgery. The other variables (bulging, stiffness, staring up, jumping, sitting/standing) did not significantly differ between the groups (P>0.05). Conclusions: Based on the results, early weight-bearing compared to delayed weight-bearing, has better outcomes in patients with ankle fractures who underwent surgical management.